PERAN UNDANG-UNDANG ITE DALAM MENANGANI KASUS CYBERBULLYNG - Yosepah Ndoa Gudu; Tanty Milan Antonia Dollu; Riven Imanuel Timo; Angel Stevanie Nafa; Fadil Mas’ud (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information technology and social media has made communication easier, but it has also given rise to various cybercrimes, one of which is cyberbullying. Cyberbullying is an act of harassment carried out through digital media and can negatively impact the psychological, social, and emotional well-being of victims. This article aims to analyze the role of the Electronic Information and Transactions Law (ITE Law) in addressing cyberbullying cases in Indonesia. The research method used is a literature review, examining various journals, laws and regulations, and related scientific sources. The results indicate that the ITE Law plays a crucial role in providing legal protection to victims, serving as a legal basis for prosecuting cyberbullying perpetrators, and raising public awareness about using social media wisely and responsibly. In addition to law enforcement, cyberbullying prevention efforts also require support from digital literacy, character education, and collaboration between the government, families, schools, and the community to create a safe and healthy digital space.